2021
DOI: 10.1049/hve2.12167
|View full text |Cite
|
Sign up to set email alerts
|

Dividing and setting strategy of improving calculation efficiency for needle electrode corona discharge with a large‐scale space

Abstract: Needle electrodes are widely used in the research of corona discharge. Aiming at the problem of needle electrode discharge in a large‐scale space (tens or even hundreds of centimetres), a hybrid model was proposed in the previous work. However, its indispensable multiple iterations result in huge computation and further limit its wide applications. Therefore, a strategy to improve the computing efficiency by setting initial values in different computational domains is put forward in this work. Three types of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Therefore, according to the different regions formed by the particle reaction of corona discharge, this paper proposes a method for region segmentation using multiple models (hybrid models), thereby extending the computational scope of discharge modes. The hybrid model uses a hydrodynamic model to calculate various particle reactions in the ionization region, and the ion mobility model calculates the particle distribution in the drift region [17,18,31]. However, all of the above are studies of a single discharge point.…”
Section: Methods Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, according to the different regions formed by the particle reaction of corona discharge, this paper proposes a method for region segmentation using multiple models (hybrid models), thereby extending the computational scope of discharge modes. The hybrid model uses a hydrodynamic model to calculate various particle reactions in the ionization region, and the ion mobility model calculates the particle distribution in the drift region [17,18,31]. However, all of the above are studies of a single discharge point.…”
Section: Methods Descriptionmentioning
confidence: 99%
“…In general, there are two ways to obtain the distribution characteristics of charged particles and electric fields: experimental measurements and numerical simulations. Experimental measurements can directly obtain charged particle concentration [17,18]. However, due to the complex electromagnetic environment, the distribution of charged particles around the electrodes cannot be obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11], the effect of three different shield configurations on the electric field distribution near the disconnecting switch break was studied and it was found that the best electric field distribution was obtained with a shield of elliptical configuration. Refs [12–14] proposed a new type of split‐box double‐break disconnector and carried out insulation strength checks. It was found that: compared to conventional disconnectors, the new split‐box double‐break disconnector has better insulation performance and higher operational reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Existing models to simulate corona discharge mainly include the plasma chemistry model [16], the hydrodynamic model [17], and the ion-migration model [18]. According to the characteristics of the above three models, a hybrid model for calculating large space corona discharge based on the hydrodynamic model and ion-migration model was proposed in our previous work [19,20]. The hybrid model divides the large computational domain into the ionization region and migration region according to the complexity of particle reaction, and calculates the physical quantities of the ionization zone and migration zone by the above two models, respectively.…”
Section: Introductionmentioning
confidence: 99%